The Mythical Conceptualization of Animal Figures in Kashan Carpets and the Shahnameh of Tahmasp from the Safavid Period (10th–11th century AH / 16th–17th century CE) within the Framework of Political Legitimacy: Representations of the Natural Order - Elaheh Panjehbashi; Negar Najibi (تاریخ نگری و تاریخ نگاری, 2023)
The most prominent manifestation of animal motifs in the history of art in the Ancient Near East up to the flourishing period of Safavid art can be observed in visual arts and crafts. The widespread use and remarkable similarities of animal motifs in the Kashan carpets and the Shahnameh of Tahmasp during the Safavid period reinforce the hypothesis that the natural world may have been conceived as a powerful source of political legitimacy for the Safavid rulers.This article aims to present a mythological interpretation of animal motifs in Kashan carpets and the Shahnameh of Tahmasp in order to gain a deeper understanding of the relationship between authority and legitimacy within the Safavid political system, and its connection to the art and culture of this period. The central research questions are as follows:What relationship can be established between mythological notions of power and the depiction of animal motifs in Kashan carpets and the Shahnameh of Tahmasp during the Safavid era? What thematic and visual similarities exist between the animal motifs of the Kashan carpets and those in the Shahnameh of Tahmasp, considering their contemporaneity, and do how they differ?This study applies a qualitative, historical-analytical method with a comparative approach. The findings reveal that the Safavid rulers attempted to reinterpret and recontextualize animal myths by incorporating them into various art forms such as manuscript illumination and carpet weaving, thereby embedding them within the structures of political power.Accordingly, the use of similar animal motifs in the Kashan carpets and the Shahnameh of Tahmasp can be seen as a deliberate engagement with mythological narratives to produce and reproduce essentialist notions of Safavid political legitimacy. The considerable similarities in the use of animal motifs in these works suggest that the Safavids, through symbolic mythological imagery, endeavored to reflect the worldview of political power discourse within Iranian art and culture.